Increasing Need for Uniqueness in Contemporary China: Empirical Evidence - Cai, Huajian; Zou, Xi; Feng, Yi; Liu, Yunzhi; Jing, Yiming (Frontiers in Psychology, 2018)
Past research has documented various cultural and psychological changes in contemporary China. In two studies, we examine how Chinese people’s need for uniqueness (NFU) also has changed. In Study 1, we found a significant cross-generational increase in Chinese participants’ self-reported NFU. In Study 2, we sampled the names of Chinese newborn babies over the last five decades and found that parents have been increasingly likely to use unique characters to name their children. These findings suggest that the NFU has been rising in China, a historically collectivistic-oriented society. Theoretical and practical implications of our findings were discussed.